Association between sleep duration and executive function differs between diabetic and non-diabetic middle-aged and older adults. (January 2020) - Titova, Olga E.; Lindberg, Eva; Tan, Xiao; Elmståhl, Sölve; Lind, Lars; Schiöth, Helgi B.; Benedict, Christian
Highlights: Association between sleep and executive function varies by diabetes. Diabetes combined with long sleep is associated with worse executive function. Short sleep is associated with worse executive function in non-diabetic subjects. Abstract: Executive function is defined as a set of cognitive skills that are necessary to plan, monitor, and execute a sequence of goal-directed complex actions. Executive function is influenced by a variety of factors, including habitual sleep duration and diabetes. In the present study, we investigated in 18, 769 Swedish adults (mean age: 61 y) the association between executive function, diabetes, and self-reported sleep duration. We observed a significant interaction between diabetes and sleep duration for the Trail Making Test (TMT) ratio (P < 0.01). This ratio is a measure of executive function where higher values indicate worse performance. Among diabetic participants (n = 1, 523), long (defined as ≥9 h per day) vs. normal sleep duration (defined as 7–8 hours per day) was associated with a higher TMT ratio (P < 0.05). Similar significant results were observed in diabetic individuals without pharmacological treatment for diabetes (n = 1, 062). Among non-diabetic participants (n = 17, 246), no association between long sleep duration and the TMT ratio was observed (P > 0.05). Instead, short (defined as <7 h per day) vs. normal sleep duration was linked to a higher TMT ratio (P < 0.05). These findings suggest that the association between sleep duration and executive function differs between diabetic and non-diabetic middle-aged and older adults. Based on the cross-sectional design of the study, no firm conclusions can be drawn on the causality of the relations.